2006
DOI: 10.1002/pd.1390
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of citrullinemia and argininosuccinic aciduria: evidence for a transmission ratio distortion in citrullinemia

Abstract: The results suggest the occurrence of preferential transmission of the mutant allele. An explanation for this phenomenon may be found in a protective role of argininosuccinic acid synthetase deficiency in mutant sperm cells against the possibly detrimental or apoptotic effect of nitric oxide produced normally from arginine by nitric oxide synthase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Elevated levels of argininosuccinic acid in the amniotic fluid can also reliably detect affected fetuses 40, 41, 42 . Analysis of enzyme activity by either direct methods from chorionic villus tissue or amniocytes or indirect methods such as 14 C-citrulline incorporation in uncultured chorionic villus samples, have been successfully performed 24, 43 .…”
Section: Diagnosismentioning
confidence: 99%
“…Elevated levels of argininosuccinic acid in the amniotic fluid can also reliably detect affected fetuses 40, 41, 42 . Analysis of enzyme activity by either direct methods from chorionic villus tissue or amniocytes or indirect methods such as 14 C-citrulline incorporation in uncultured chorionic villus samples, have been successfully performed 24, 43 .…”
Section: Diagnosismentioning
confidence: 99%
“…However, compound heterozygous carriers of some of these mutations (Ivs15-1G4C, R157C, V263M, E283K, G324S, R363W, and G390R) have been identified who, owing to the function of the second allele, present only mild clinical symptoms [Gao et al, 2003;Häberle et al, 2002;Hong et al, 2000;Sander et al, 2003]. A total of 30 mutations occur in compound heterozygotes with neonatal onset of citrullinemia [Gao et al, 2003;Häberle et al, 2002;Kakinoki et al, 1997;Kleijer et al, 2006;Kobayashi et al, 1990Kobayashi et al, , 1991Kobayashi et al, , 1994Li et al, 2001;Vilaseca et al, 2001]. Again, some of these aberrations-such as G14S, G117D, and E191Q-were also revealed to account for mild or late onset forms of the disease.…”
Section: Mutations and Polymorphismsmentioning
confidence: 99%
“…A total of 17 mutations have been shown to cause neonatal onset of the disorder when found in a homozygous state (see Table 1) [Gao et al, 2003;Kakinoki et al, 1997;Kleijer et al, 2006;Kobayashi et al, 1990Kobayashi et al, , 1991Kobayashi et al, , 1994Kobayashi et al, , 1995Sander et al, 2003;Vilaseca et al, 2001]: among them are two nonsense mutations in addition to four splice-site defects, two deletions, and seven missense mutations. However, compound heterozygous carriers of some of these mutations (Ivs15-1G4C, R157C, V263M, E283K, G324S, R363W, and G390R) have been identified who, owing to the function of the second allele, present only mild clinical symptoms [Gao et al, 2003;Häberle et al, 2002;Hong et al, 2000;Sander et al, 2003].…”
Section: Mutations and Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest the occurrence of preferential transmission of the mutant allele compared to the normal allele. Kleijer et al (2006) suggested that this phenomenon could be explained by a protective role of ASS deficiency in mutant sperm cells against the possible detrimental or apoptotic effect of nitric oxide produced normally from arginine by nitric oxide synthase.…”
Section: Resultsmentioning
confidence: 99%